2021
DOI: 10.1007/s40328-020-00331-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal horizontal deformations obtained using GPS and GRACE data: case study of North-East India and Nepal Himalaya

Abstract: The area of NorthEast India and Nepal Himalaya undergoes seasonal deformations due to the variation of surface mass loads induced mainly by annual monsoon precipitation. The present study focuses on comparing seasonal horizontal deformations of the Earth's surface obtained over the area of NorthEast India and Nepal Himalaya using Global Positioning System (GPS) and the corresponding ones obtained from Gravity Recovery and Climate Experiment (GRACE) satellite mission data. Seasonal deformations of the Earth's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Most of the studies that have examined hydrologic loading solely using horizontal deformation were located in areas known to have large hydrologic loads (and thus large GNSS‐recorded vertical deformation), namely the Amazon Basin and Southeast Asia (Bettinelli et al., 2008; Chanard et al., 2014; Fu et al., 2013; Ray et al., 2021). However, a few studies have demonstrated the utility of analyzing both horizontal and vertical surface deformation.…”
Section: Water Storage Estimation From Gnss Observations Of Surface D...mentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies that have examined hydrologic loading solely using horizontal deformation were located in areas known to have large hydrologic loads (and thus large GNSS‐recorded vertical deformation), namely the Amazon Basin and Southeast Asia (Bettinelli et al., 2008; Chanard et al., 2014; Fu et al., 2013; Ray et al., 2021). However, a few studies have demonstrated the utility of analyzing both horizontal and vertical surface deformation.…”
Section: Water Storage Estimation From Gnss Observations Of Surface D...mentioning
confidence: 99%
“…Horizontal movement from hydrologic loading is generally an order of magnitude less than long-term tectonic movement; therefore, horizontal displacements recorded by GNSS are most commonly used to estimate secular crustal velocities to constrain tectonic-plate motion as well as coseismic and post-seismic deformation due to earthquakes ( Ray et al, 2021 ). Furthermore, Borsa et al ( 2014) note the use of vertical-to-horizontal displacement ratios to identify GNSS stations experiencing tectonic or volcanic motion where horizontal motion exceeds vertical motion.…”
Section: Comparing Vertical and Horizontal Displacementsmentioning
confidence: 99%
See 2 more Smart Citations